Dampak Kenaikan Harga BBM Terhadap Biaya Operasional UMKM: Studi Kasus Mendalo Darat - Hermalia Putri; Febrina Noviyanti; Nia Ramadhani; Rifki, Ahmad; Rizal Iskandar; Elvrida Davita Tamba; Chandra Putra Nur Fajar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2025)
This study aims to analyze the impact of the fuel price increase, triggered by the surge in global oil prices and subsidy reduction policies, on the production, distribution, and transportation costs of MSMEs. The methodology employed is a qualitative approach using semi-structured interviews and field observations. The results indicate that the rise in fuel prices led to increased operational costs, decreased purchasing power of the community, and reduced sales and profitability of MSMEs. MSME operators responded with various adaptation strategies, such as reducing the portion or quality of materials, holding prices steady, and seeking alternative suppliers. Although fuel prices have stabilized, the residual effects of the previous price increases are still felt, with cost structures remaining high. This research emphasizes the importance of the government's role in providing support and protection for MSMEs, as well as the need for national energy policies that consider local realities to create better social and economic justice.